Periodically-segmented liquid crystal core waveguides. (31st August 2017) - Sharma, Mukesh; Shenoy, M R; Sinha, Aloka
Abstract: We report the fabrication and characterization of electrically-tunable periodically segmented waveguides (PSWs) with different duty cycles of 0.25, 0.33, 0.50 and 0.76, using the nematic liquid crystal 5CB as the guiding layer, and the negative photoresist AZ15nXT as the cladding. The experimental results show that light diffracts and re-focuses periodically on propagation through the liquid crystal (LC) core PSW, when an external voltage is applied to the periodically segmented electrodes. The performance of the fabricated LC core PSWs are analyzed in terms of effective refractive index, output power and duty cycle. The electrically-tunable LC core PSWs have potential application in the realization of optical filters, polarizers and dynamic mode size converters.